Effectiveness of modified clear aligner designs in mesialization of permanent molars: a typodont model study - Al Ali, Sara Mohamed; Ghoneima, Ahmed (Frontiers in Dental Medicine, 2025)
IntroductionClear aligner therapy has evolved significantly as an aesthetic and comfortable alternative to conventional fixed orthodontic appliances. However, the predictability of certain complex tooth movements such as bodily mesialization of molars remains a subject of ongoing investigation. This study explored the efficacy of clear aligners made from shape memory polymer (Graphy Tera Harz TC-85DAC resin) in achieving mesialization of the upper first molar.MethodsThis in vitro study was conducted using typodont models with an extracted upper second premolar. Digitally designed clear aligners were fabricated using shape memory polymer. Four groups were assessed based on attachment design: no attachments, buccal attachment, palatal attachment, and both buccal and palatal attachments. The aligners were designed to move the upper first molar mesially by 3 mm. Pre- and post-treatment positions of the molars were measured and analyzed to determine the nature and extent of tooth movement.ResultsAll groups demonstrated mesial movement of the upper left first molar; however, only Groups 1 (no attachments) and 2 (buccal and palatal attachments) achieved the planned 3 mm movement. Groups 3 and 4 exhibited slightly less movement. The distance between the upper first molar and upper first premolar reduced significantly in all groups (P < 0.001). All groups showed mesial tipping rather than bodily movement of the molar. No attachment configuration was able to produce controlled root movement into the space.ConclusionThe modified clear aligner design fabricated from shape memory polymer (Graphy material) induced mesial tipping of the upper first molar but failed to achieve bodily mesialization. Further research is necessary to optimize aligner design and biomechanical strategies to enable more predictable control in mesial molar movement.